Biointerfaced sensors for biodiagnostics. Issue 4 (6th April 2021) - Zohar, Orr; Khatib, Muhammad; Omar, Rawan; Vishinkin, Rotem; Broza, Yoav Y.; Haick, Hossam
ABSTRACT: Biointerfaced sensors have emerged as a new paradigm for medical applications that require an interface and/or intimate contact with biological components/systems such as cells, tissues, and whole organs. This article provides a review of the concept, design, and device characteristics of biointerfaced sensors needed for successful implementation of biodiagnostics and monitoring. It begins by presenting and discussing the different considerations that arise from artificial interfaces with different biological environments. It then explores the main strategies for sensor and material design, while highlighting the required chemistry, structure, and mechanical properties needed to maintain an unperturbed interface with the surrounding biological environment. Finally, the review discusses successful state‐of‐the‐art demonstrations of body monitoring and biodiagnostics, focusing on the brain, heart, muscles, skin, teeth, and other tissues for medical purposes. Insights, perspectives, and recommendations for future research are presented. Abstract : This review aims to present a broad overview of new biointerfaced sensors for biodiagnostic applications. The authors begin by providing the principles of biointerfaced sensors, going over sensor structure and biocompatibility concerns. They then go over the different biodiagnostic applications and possible stimuli that can be targeted.